Communicating waste sorting with newly-arrived immigrants - Hija Uhlås, Asya (2021)
This thesis explores communication on waste management to the newly-arrived immigrants. Communicating waste sorting to the newly-arrived immigrants is challenging because it involves multiple senders and multiple receivers, where culture, knowledge and language needs to interplay. The thesis shows how different groups of immigrants get information in waste sorting and suggests how other groups may be left out without being communicated. There is information gap between the sender and the receiver, and also between different receivers.